2016
DOI: 10.1002/advs.201500263
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Silicon Nanocrystals with Colloidal Stability, pH‐Independent Positive Surface Charge and Size Tunable Photoluminescence in the Near‐Infrared to Red Spectral Range

Abstract: In this report, the synthesis of a novel class of cationic quaternary ammonium‐surface‐functionalized silicon nanocrystals (ncSi) using a novel and highly versatile terminal alkyl halide‐surface‐functionalized ncSi synthon is described. The distinctive features of these cationic ncSi include colloidal stability, pH‐independent positive surface charge, and size‐tunable photoluminescence (PL) in the biologically relevant near‐infrared‐to‐red spectral region. These cationic ncSi are characterized via a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…First, there is a need for a method to deliver netrin‐1 and control its release through the resistance caused by blood flow that also allows small‐diameter TEBVs to capture EPCs from circulation to promote endothelialization. The results showed that the multilayered collagen‐chitosan nanoparticles containing netrin‐1 successfully bonded to small‐diameter TEBVs, which also enhanced their strength and stabilization due to the ionic bond between the carboxylic acid of collagen and amino group of chitosan . In vivo, the results showed netrin‐1 was released evenly for 30 d.…”
Section: Discussionmentioning
confidence: 96%
“…First, there is a need for a method to deliver netrin‐1 and control its release through the resistance caused by blood flow that also allows small‐diameter TEBVs to capture EPCs from circulation to promote endothelialization. The results showed that the multilayered collagen‐chitosan nanoparticles containing netrin‐1 successfully bonded to small‐diameter TEBVs, which also enhanced their strength and stabilization due to the ionic bond between the carboxylic acid of collagen and amino group of chitosan . In vivo, the results showed netrin‐1 was released evenly for 30 d.…”
Section: Discussionmentioning
confidence: 96%
“…Photoluminescent nanomaterials (PLNMs) are extensively used in various biomedical fields such as biosensing, bioimaging, diagnostics, and therapy. Compared to organic fluorescent molecules, PLNMs have higher photostability and larger tunable emission wavelength range and have thus gained much attention in recent years. Although various PLNMs including semiconductor quantum dots, noble metal nanoclusters, upconversion nanomaterials, , polymer dots, silicon-containing nanomaterials, and carbon/graphene quantum dots have been synthesized, their biomedical applications are usually limited because of many drawbacks such as potential cytotoxicity, low photoluminescence (PL) quantum efficiency, complicated synthetic procedures, broad PL emission peaks, poor water dispersibility, difficulty of modification, and high cost. Therefore, it is urgently needed to develop new PLNMs with superior physicochemical, optical, and biocompatible properties to overcome the above-mentioned shortcomings.…”
mentioning
confidence: 99%
“…Ordered arrays of ligand-stabilized nanocrystals, or superlattices, have been made from many different kinds of materials, with a diverse range of nanocrystal shapes, including spheres, rods, disks, and even tetrapods, by self-assembly at solid or liquid interfaces, or as free-standing films, by evaporating the solvent from concentrated dispersions. Superlattice formation requires only that the nanocrystals are uniform in size and shape and well-dispersed in the solvent. Because of the size-dependent properties of the nanocrystals and the emergent collective behavior of their assemblies, superlattices have been explored for numerous applications. One approach of making significant quantities of well-characterized Si nanocrystals involves an initial high temperature reactant (hydrogen silsesquioxane, HSQ) decomposition and nanocrystal formation step followed by alkene surface passivation by hydrosilylation. Si nanocrystals are generated with sufficient uniformity to enable a subsequent size-selective precipitation to provide the monodispersity needed for superlattice assembly. Like other semiconductor quantum dots, Si nanocrystals exhibit size-tunable visible luminescence and optoelectronic properties , but are much more stable at elevated temperatures because of the strong covalent Si–C bonding of their hydrocarbon capping ligands . Si nanocrystals are also biocompatible and nontoxic, making them appealing for commercial applications. However, even with a uniform size, Si nanocrystals do not self-assemble into superlattices as readily as other kinds of nanocrystals, typically requiring long drying times (>30 min), perhaps as a result of weaker van der Waals attractions between Si cores than other types of more polarizable materials, such as ionic solids and especially metals .…”
Section: Introductionmentioning
confidence: 99%